Validation of GPSkin Barrier® for assessing epidermal permeability barrier function and stratum corneum hydration in humans. Issue 1 (4th June 2018) - Ye, L.; Wang, Z.; Li, Z.; Lv, C.; Man, M.‐Q.
Abstract: Background: Measurements of transepidermal water loss (TEWL) and stratum corneum (SC) hydration are important for assessing epidermal functions. However, the availability of reliable and user‐friendly devices, which can simultaneously measure both TEWL and SC hydration and can allow health providers to remotely access data in time, is limited. Materials and Methods: GPSkin Barrier ® was compared with MPA5 system in the measurements of TEWL and SC hydration on the cheek, the dorsal hand, and the forearm in 200 normal volunteers, including 126 females and 74 males, aged 1‐78 years with an average age of 45.24 ± 1.04 years. Correlation of data measured with MPA5 system and GPSkin Barrier ® was determined. Results: Levels of both TEWL and SC hydration measured with the Barrie GPSkin Barrier ® were lower than that with MPA5 system on all 3 body sites except for hydration on the cheek. The levels of both TEWL and SC hydration measured with GpSkin Barrier ® were correlated well with that measured with MPA5 system on all 3 body sites Conclusions: GPSkin Barrier ® is a reliable, affordable, and versatile device for assessing epidermal permeability barrier function and SC hydration.